IMPLEMENTASI KEBIJAKAN TRANSISI PAUD DI SEKOLAH DASAR INKLUSI BERDASARKAN PRINSIP MULTIKULTURAL : PELUANG DAN TANTANGAN - Muliati Mursak; Arifin Maksum; Nina Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Multiculturalism in inclusive schools is an essential requirement for teachers and other school staff to facilitate the learning process for children with diverse characteristics. This study aims to examine the implementation of the early childhood education (PAUD) to elementary school transition policy at SDN 9 Banawa, Central Sulawesi, as an inclusive school by focusing on the application of multicultural principles. The study employed a descriptive qualitative method with a case study approach. Research subjects included teachers, the school principal, supervisors, and parents. Data collection techniques were carried out through in-depth interviews and documentation. The research was conducted in September 2024. Data analysis used the interactive model developed by Miles and Huberman (1984), consisting of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the transition policy from PAUD to elementary school at SDN 9 Banawa aligns with the regulations set by the Indonesian Ministry of Education. The policy's implementation is also adapted to inclusive and multicultural principles, which is reflected in activities that instill the six foundational values in children, particularly the second and sixth foundational